1974
DOI: 10.1111/j.1365-2133.1974.tb12450.x
|View full text |Cite
|
Sign up to set email alerts
|

The syndrome of chronic photosensitivity dermatitis and actinic reticuloid

Abstract: SUMMARY In a Study of thirty‐four male subjects suffering from the syndrome of chronic photosensitivity dermatitis and actinic reticuloid the clinical, histological and photobiological features were such as to suggest that they were in fact examples of a single entity in which the degree of response to ultraviolet and visible light varied. Although a wide action spectrum involving UV and visible wavelengths invariably occurred with the classical clinical and histological features of actinic reticuloid (Ive et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

1978
1978
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(40 citation statements)
references
References 6 publications
2
37
0
1
Order By: Relevance
“…2,[5][6][7]14 The absence of diagnostic phototesting facilities in some regions may lead to CAD not being recognized, with, for example, only the allergic contact dermatitis component being diagnosed. Nevertheless, CAD probably occurs worldwide.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[5][6][7]14 The absence of diagnostic phototesting facilities in some regions may lead to CAD not being recognized, with, for example, only the allergic contact dermatitis component being diagnosed. Nevertheless, CAD probably occurs worldwide.…”
Section: Commentmentioning
confidence: 99%
“…2000;136:1215-1220 P ATIENTS WITH chronic actinic dermatitis (CAD), 1 also known as the photosensitivity dermatitis and actinic reticuloid syndrome, 2 are abnormally photosensitive to UV (UV-B and UV-A) and often visible wavelengths. Studies from Europe reported that most patients also have allergic contact dermatitis, [3][4][5][6] although this has been detected in a lower proportion in a North American series.…”
mentioning
confidence: 99%
“…The positive photopatch reaction to Parthenium will, however, favour the diagnosis of a photocontact dermatitis. Photopatch reactions have been reported in the past by F r a in -B ell et al [1] in patients with actinic reticuloid. It is quite possible that some patients with chronic photosensitivity, from whatever cause, may result in a clinical and histological picture simulating actinic reticuloid.…”
Section: Commentmentioning
confidence: 90%
“…This and other compositae dermatitis have been reported to resemble photodermatitis [1,2], Lonker et al [3] contend that despite superficial resemblance to photodermatitis in some of their patients, the evidence is in favour of Parthenium dermatitis being an allergic contact dermatitis exaggerated by sunlight. In the course of our clinical practice we have long suspected that a true photocontact dermatitis caused by Parthenium probably exists.…”
mentioning
confidence: 99%
“…In severe cases it may become generalized and develop a pseudolymphomatous appearance. 22 Abnormal MEDs are found on monochromator light testing. UVB photosensitivity is present in virtually all patients, UVA in most and visible light in some.…”
Section: Acquired Photodermatosesmentioning
confidence: 98%